Absence from work or school in young adults with congenital heart disease: is illness identity associated with absenteeism?. (2nd December 2021) - Na, Inwon; Van Bulck, Liesbet; Rassart, Jessica; Goossens, Eva; Luyckx, Koen; Van De Bruaene, Alexander; Moons, Philip
Abstract: Aims: Absence from work or school in patients with congenital heart disease (CHD) is an understudied domain. Illness identity, which is the degree to which a chronic illness is integrated into one's identity, could be hypothesized to be a predictor for absenteeism. This study determined the proportion of young adults with CHD absent from work or school and examined if illness identity dimensions were related to absenteeism. Methods and results: In a cross-sectional study, we included 255 patients with CHD. Data on absence from work or school over the past 12 months were obtained using self-report. The Illness Identity Questionnaire was used, which comprises four illness identity dimensions: rejection, engulfment, acceptance, and enrichment. Linear models with doubly robust estimations were computed after groups were balanced using propensity weighting. Absence from work/school occurred in 69% of young adults with CHD. Absence because of CHD specifically was present in 15% of the patients. Engulfment was significantly related to both all-cause absence and absence for CHD reasons. Conclusions: Patients who strongly define themselves in terms of their heart disease were more likely to be absent from work or school than those who did not. If this finding can be confirmed in future research, it has the potential to be a target for intervention to influence work/school absence.